Emphase prosodique et emphase syntaxique : le cas de « do » dans un corpus de parole naturelle. - Sophie Herment (Corela)
The present study focuses on the links between prosody and syntax in a corpus of natural speech through the analysis of “emphatic do”, i.e. the auxiliary “do” inserted in an affirmative context. The occurrences of “emphatic do” in the Aix-Marsec corpus (5h30 of natural speech) are analysed first linguistically and then acoustically and prosodically. Three different linguistic categories are distinguished, depending on the role of “do” at the level of the predicative relation, and acoustic and prosodic measures are taken: length of the initial consonant, pitch, tone. The prosodic realisation of “emphatic do” is shown to be different according to whether “do” reinforces or denies the predicative relation given before. It is also shown that a few occurrences of “do” are totally unaccented. We conclude that prosody and syntax both play important roles for emphasis and focalisation but at different levels: they are revealed complementary and the association between those two levels enables the speaker to play on the semantic subtleties of discourse.